MIL ROSAS ROUBADAS, WORK OF SILVIANO SANTIAGO: A BAKHTINIAN ANALYSIS - Marchezan, Renata Coelho [UNESP]; Pernambuco, Juscelino (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2017)
This article analyzes Mil rosas roubadas, written by Silviano Santiago in 2014, dealing with the notions of (auto) biography, (auto) biographical novel, metafiction and autofiction. Although the creation of this last word may indicate the existence of a new genre - it is even adopted by the writer himself to name his work -, the article shows the pertinence of placing Mil rosas roubadas in the route of the transformations and stylisations of the (auto) biographical novel, such as examined by M. Bakhtin. The novel is, for Bakhtin, a genre without rigid forms, an unfinished genre, as it always follows the inflections of social life. In this way the ressemantization of the self, proposed by Silviano Santiago, is analyzed.
Keywords: Silviano Santiago; Bakhtin; (auto) biographical novel; Metafiction; Autofiction